INTEGRATING CHARACTER EDUCATION AND LOCAL WISDOM IN DEVELOPING ENGLISH TEACHING MATERIAL - Muawwinatul Laili (Universitas Nahdatul Ulama Surabaya, 2017)
There are many moral degradations has influenced students’ character. Character education need to be implemented in students’ learning activities. However, some teachers find some difficulties in finding and creating a textbook that includes character education in it. Besides, the role of local wisdom is very important in teaching character education and shaping students’ identity. The teachers can promote local wisdom through English teaching materials. Both of charactereducation and local wisdom can be integrated in the teaching materials. This research intends to develop English teaching material needed by eighth graders. The design to develop the teaching material is Research and Development (R & D). The R&D method procedure that was conducted by the researcher is adapted from Cunningham’s R&D in Borg and Gall (2003). The development process was done by six steps, they are; reviewing relevant of literature, planning the chapterobjectives, developing a preliminary form, field-testing the preliminary form, revising the preliminary form based on the field-test results, and conducting a main field test of the revised form. As the result, the final products that integrated with character education and local wisdom can be the solution to promote the local wisdom and the way to teach character to the students.